How Are Firms Responding to Philippine FTAs? - Rafaelita M. Aldaba; Erlinda M. Medalla; Josef T. Yap; Maureen Ane D. Rosellon; Fatima del Prado; Melalyn C. Mantaring; Veredigna M. Ledda (Philippine Institute for Development Studies (PIDS), 2015)
The Philippines has been more cautious in its policy toward free trade agreements (FTAs) than other ASEAN member-states, having signed, so far, only one bilateral agreement with Japan in addition to the various ASEAN+1 agreements. While the government is expected to progressively reduce preferential tariffs to zero, Philippine firms have historically been slow to take advantage of FTAs. This survey reaffirms that this awareness and the usage of FTAs need significant improvement among both manufacturing and services sector firms.Identified as the main source of information for FTAs, the government needs to increase the efficiency, scope, and reach of its promotional and technical training programs and to rely further on technology to deliver results. These efforts to enhance FTA utilization are directly linked with the easing of rules of origin (ROOs) compliance and administration. At the national level, these efforts include reforms toward electronic Certificates of Origin and self-certification, and linkage to the national single window. This will improve timelines and ease the entry of micro, small, and medium enterprises. Regional efforts to harmonize ROOs can increase FTA utilization across ASEAN member-countries and pave the way for the forthcoming Regional Comprehensive Economic Partnership.
Keywords: F1; F2; F6; F61; 330; Philippines; free trade agreements (FTAs); Certificate of Origin; FTA utilization